2018
DOI: 10.1017/s0022109018000352
|View full text |Cite
|
Sign up to set email alerts
|

Hedge Fund Boards and the Market for Independent Directors

Abstract: We provide the first examination of hedge fund boards and their directors. The majority of directorships are held by extremely busy independent directors. These directors are sought by funds because they have more reputational capital at stake, making them independent and credible monitors whose presence can certify fund quality to investors. Busy independent directors are more likely to be hired by high-quality funds, and their departure from the board is associated with investor withdrawals. Moreover, funds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This, in turn, leads to high market valuations. Our finding is consistent with prior literature within the industrial sector settings (e.g., Ammann et al 2011;Field et al 2013;Clifford et al 2017). The absence of market valuations for IBs can be justified through the signalling theory.…”
Section: Market Valuations Of Busy Boards Of Directors In Islamic and Conventional Bankssupporting
confidence: 92%
See 1 more Smart Citation
“…This, in turn, leads to high market valuations. Our finding is consistent with prior literature within the industrial sector settings (e.g., Ammann et al 2011;Field et al 2013;Clifford et al 2017). The absence of market valuations for IBs can be justified through the signalling theory.…”
Section: Market Valuations Of Busy Boards Of Directors In Islamic and Conventional Bankssupporting
confidence: 92%
“…Busy directors thus can be assessed as valuable assets for their firms given their extensive and updated industry-specific knowledge. This board can, hence, offer a vital supportive role to inside directors (Clifford et al 2017) as well as have established outside networks that could facilitate access to market sources and other strategic benefits. These reputational benefits can be positively priced by investors, and board busyness can be perceived as value-enhancing for a firm (Muravyev et al 2016).…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…Independent directors aim to supervise the business decisions of enterprises to ensure an independent director system (Napitupulu et al, 2020;Taghavi Moghaddam et al, 2018). The independence that comes with their identities and their characteristics as outsiders helps them exercise their supervisory and decision-making functions objectively and impartially (Clifford et al, 2018;Pucheta-Martínez et al, 2019;Yu et al, 2018). Independent directors can make objective and fair decisions when weighing the interests of shareholders and other stakeholders, as they do not have close ties with the parties involved.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…Coville and Kleinman (2015), based on a set of US firms, during the period 1999 to 2006 found that board characteristics, including the proportion of independent directors, positively impacted dividend pay-out of the sample firms. Clifford et al (2017), for a set of hedge funds registered with the securities and exchanges commission, during the period 2009 to 2013, concluded, that the funds with independent directors were linked to the reduction in fraud activity. Shawtari et al (2017) assessed a set of Malaysian firms for the period 2002-2011 and established that board independence (measured through the PNED) positively influenced the real performance measured through operating income.…”
Section: Literature Review Theoretical Framework and Development Of Hypothesismentioning
confidence: 99%